Keeneland's Ted Bassett : My Life - Bassett, James E. (James Edward), 1921- (Book collections on Project MUSE., 2009)
Founded in 1935, Keeneland is widely regarded by horseracing enthusiasts and professionals as one of the world's premier racetracks. Its April and October race meetings and its annual public thoroughbred auctions lure participants from around the world. By far, James E. ""Ted"" Bassett III is the man whose name is most frequently linked with Keeneland's extraordinary history and success. Bassett's involvement with Keeneland began in 1968, after he served in the U.S. Marine Corps during World War II and was director of the Kentucky State Police during the tumultuous mid-1960s. Since 1968, Basse